Laboratory Research of Multiple Flow Movement in Pipelines - Makhkamov DA; Chorshanbiev UR; Babaev AR (Global Scientific Publishing, 2022)
In mining and processing enterprises, the properties of sludge flow mixtures are determined primarily by the particle size distribution and bulk concentration of solid particles. The constant interaction of liquid and solid particles requires the determination of the pressure drop and the flow rate. Existing methods of hydrotreating of turbid liquids are based on the laws of turbulent motion and the empirical and semi-empirical relationship between kinematic and dynamic flow parameters such as particle size distribution, concentration and critical velocity of solid particles.
Keywords: Dispersion system; flow; velocity; order of motion